Lysine and arginine requirements of Salminus brasiliensis - Dairiki, Jony Koji; Borghesi, Ricardo; Dias, Carlos Tadeu dos Santos; Cyrino, José Eurico Possebon (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to determine the dietary lysine (DL) and dietary arginine (DA) requirements of dourado (Salminus brasiliensis), through dose‑response trials using the amino acid profiles of whole carcasses as a reference. Two experiments were carried out in a completely randomized design (n=4). In the first experiment, groups of 12 feed‑conditioned dourado juveniles (11.4±0.2 g) were stocked in 60 L cages placed in 300 L plastic indoor tanks in a closed circulation system. Fish were fed for 60 days on diets containing 1.0, 1.5, 2.0, 2.5, 3.0, or 3.5 % dietary lysine. In the second experiment, dourado juveniles (27.0±0.8 g) were fed for 60 days on semipurified diets containing arginine at 1.0, 1.5, 2.0, 2.5 or 3.0%, in similar conditions to those of the first experiment. Optimal DL requirements, as determined by broken‑line analysis method for final weight, weight gain and specific growth rate, were 2.15% DL or 5% lysine in dietary protein, and 1.48% DA or 3.43% arginine in dietary protein. The best feed conversion ratio is attained with 2.5% DL or 5.8% lysine in dietary protein and 1.4% DA or 3.25% arginine in dietary protein.